Green Synthesis of Magnesium Oxide (MgO NPs) and Adsorption with Eosin Dye - H. Obaid, Alieaa; M. Hussein, Fadhila; A. Abbas, Salma; A. Jawad, Asmaa; A. Ibrahim, Tahseen (Al-Nahrain Journal of Science, 2022)
The green synthesis method is used to create magnesium oxide (MgO) nanoparticles in this study. SEM measurements and X-ray diffraction techniques are used to determine their crystal structure, as well as, FTIR to analyze the MgO na articles. Green synthesis of MgO nanoparticles are a good adsorbent for Eosin dye in aqueous solutions. Contact time, adsorbent mass, temperature, and Eosin dye concentration were all investigated. Freundlich isotherm models and the Eosin dye isotherm adsorption were well identical. The thermodynamic research yielded 101.4152 J/mol K, 0.02826397 kJ/mol, and -30.7005537 kJ/mol for the ΔS, ΔH and ΔG parameters, respectively. moreover, with R2 = 0.9228, the kinetic investigation revealed that the adsorption was pseudo-second-order.